2013
DOI: 10.4236/abb.2013.412145
|View full text |Cite
|
Sign up to set email alerts
|

Sex effect on presenilins expression in post-natal rat brain

Abstract: Presenilin 1 and presenilin 2 are widely expressed during brain development. Several mutations in these proteins have been associated with autosomal-dominant inherited forms of Alzheimer disease. Their expression is regulated by various cellular and extracellular factors, which change with age and sex. Both age and sex are key risk factors for Alzheimer's disease, but the issue of whether the expression of presenilins is influenced by the sex during early postnatal development of the brain has been poorly inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Coronal sections (thickness, 8 μm) obtained at −2,00 mm from bregma were processed as previously described [51,52,55]. Briefly, antigen retrieval was achieved by pre-treating sections with 10 mM sodium citrate pH 6.0 in a microwave oven for 5 min; then, sections were incubated overnight at 4°C with a mouse monoclonal primary antibody against PSEN1 (#MAB5232, Millipore; 1:500 final dilution in PBS), washed 5 times with PBS, and stained using the mouse Vectastain Elite ABC Kit (Vector Laboratories Inc., cat.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Coronal sections (thickness, 8 μm) obtained at −2,00 mm from bregma were processed as previously described [51,52,55]. Briefly, antigen retrieval was achieved by pre-treating sections with 10 mM sodium citrate pH 6.0 in a microwave oven for 5 min; then, sections were incubated overnight at 4°C with a mouse monoclonal primary antibody against PSEN1 (#MAB5232, Millipore; 1:500 final dilution in PBS), washed 5 times with PBS, and stained using the mouse Vectastain Elite ABC Kit (Vector Laboratories Inc., cat.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In present study, male mice were used. In earlier report, Piscopo et al (2013) showed altered expression of PS1 and PS2 at postnatal stages of rat cerebral cortex development. The alteration in expression pattern was similar in male and female for PS1 as well as PS2 during development but the extent of alteration was variable.…”
Section: Proteinmentioning
confidence: 72%